Identification of sex linked molecular markers in Indonesian giant freshwater prawn Macrobrachium rosenbergii - Novi Megawati; Alimuddin; Ratu Siti Aliah (Jurnal Akuakultur Indonesia)
Male giant freshwater prawn grows faster than its female. Therefore, male mono sex culture is one of the solutions to improve aquaculture production. The all-male population of giant freshwater prawns can be produced by mating the neo-females (sex-reversed males) with the normal males. This study was aimed to identify the molecular markers related to the giant freshwater prawn sex. Specific primers were designed based on female-specific AFLP marker sequences to distinguish male and female sex on the prawns. Three locations for obtaining the Indonesian prawns in this study were Aceh, Sukabumi, and Solo. Based on the PCR analysis with MrMKn primers, 30 samples of female prawns had 100 % occurred DNA bands, while no DNA bands were obtained in all-male prawns from Solo. Nevertheless, MrMKn primers still detected 10–16 % male prawns from Sukabumi and Aceh. This indicated that MrMKn primers could not yet distinguish the male prawns for all populations. Moreover, the results suggested that the three prawn samples were different based on female-specific gene sequence. The MrMKn primers have the opportunity to be used in the selection of the female ZZ (neo-female) prawns from Solo without progeny test, so that the determination of female ZZ candidates can be identified more quickly. However, the primer still needs to be redesigned to distinguish neo-female prawns from Sukabumi and Aceh.